Measurement Of Social Fund Assistance Program And Economic Indicators Of Bangka Belitung Islands In The Effort To Reduce Poverty Rate - Julia Julia; Khairiyansyah (Future Science, 2021)
This study aims to analyze the relationship and influence of social assistance on the number of poor people in the Province of the Bangka Belitung Islands. There are control variables as comparison, namely; unemployment, central government debt, economic growth and poverty. The research method uses a quantitative approach with non-parametric statistics, annual data (2015-2020) and elasticity are used to measure the magnitude of change in the number of poor people due to additional social assistance. Spearman Rank test to examine the relationship of each variable (the number of unemployed, central government debt and economic growth) to the amount of poverty in Indonesia. The results of the study show that there is a very strong relationship between social assistance for Contribution Assistance Recipients and the Family Hope Program on the number of poor people. A negative sign indicates that social assistance can significantly reduce poverty, with the strongest impact being the program. There is a strong relationship between debt and the number of poor people. The slowdown in economic growth has been proven to be unrelated to the number of poor people. This means that, in the midst of an economic slowdown, the number of poverty in Indonesia can be reduced through social assistance programs, job creation as laborers and government debt is allocated for productive activities and economic activities that have a direct impact on the poor and the poor. vulnerable to poverty.